The Antibacterial activity of Pistacia Khinjuk resionous exudates - Al-jaff, Bahrouz M. A. (Sulaimani Journal for Pure and Applied Sciences, 2003)
A crude resinous exudate from Pistacia lentiscus related Pistacia khinjuk tree distributed in Kurdistan mountains has been used focally in curing some lesions including burns. The preparation solved in 50% ethanol and diluted by distilled water was appeared to have antibacterial activity. The minimum inhibitory concentration (MIC) of the resin by well diffusion agar for Staphylococcus aureus was 50 pg/ml and with no effect on P. aeruginosa. By dilution broth method, MIC was 125 pg/ml for S. aureus and 500 pg/ml for P. aeruginosa .The killing effect against P. aeruginosa occurs also by the solvent 50% ethanol which revealed that resin has no effect on this species. The minimum bactericidal concentration was the same of MIC for both species. The effect of resin was not belonged to phenol only that the MIC of phenol by well diffusion agar was lower than resin for S. aureus.
Keywords: Pistacia khinjuk; Pistacia lentiscus; mastic; resin; antibacterial activity; bacteria; Staphylococcus aureus; Pseudomonas aeruginosa